Analisis Yuridis Pemutusan Hubungan Kerja Sepihak Melalui Pesan Whatsapp (Studi Putusan Pengadilan Nomor: 5/Pdt.Sus-PHI/2023/PN Gresik) - Mochammad Luthfan Adilin; Rini Winarsih; Muhammad Chalil (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2023)
Labor means every person who is able to do work to produce goods and/or services to meet their own needs or the needs of society, while the definition of worker means every person who works to get money or other forms of compensation. WhatsApp Messenger is used as a means for various important activities, such as buying and selling transactions, renting and various civil activities which give rise to rights and obligations for the parties. However, currently there are several cases, including termination of employment or layoffs by employers of their workers or workers whose means of notification is via the WhatsApp application and employers who carry out layoffs unilaterally because the workers/workers are deemed to have committed disciplinary action. In this case the researcher used Court Decision Number: 5/Pdt.Sus-PHI/2023/PN Gresik as secondary data. In one case, not only the notification was made via WhatsApp Messenger, but the delivery of the decision to terminate employment was also carried out via WhatsApp. This incident occurred with Hadiono who received notification of Termination of Employment via WhatsApp Messenger.